Gamifying Software Testing – A Focus on Strategy & Tools Development - Memar, Navid (Curtin University, 2019)
This study aims to introduce new software testing strategies and tools with the aim of creating a more engaging and rewarding environment for software testers. For this purpose, gamification has been selected as a potential solution to raise the performances of testers. Empirical experiments were conducted to validate key factors and metrics influencing the design and development of a gamified software testing system.